Comparative study of composite scarf and strap joints for equivalent repair signature under uniaxial tension - Srinivasan, Dharun Vadugappatty (2022)
Scarf joints are preferred in aerospace composite repairs that offer better strength, flushed surface and nearly uniform shear and peel stress distribution along the bond length. However, a shallow scarf angle repair of 2° to 3° as practiced requires significant parent material removal thus increasing the repair signature and cost. Scarfing the single side accessible, multi-layered composite structures is difficult. Herein, different repair designs based on 8.6° scarf, thin CFRP strap (0.5 mm and 1.1 mm), 0.5 mm thin Ti-6Al-4V straps (with and without pins) are used in bonding CFRP composites, their repair strength is measured through tensile testing. Results show that the failure load of the scarf and Ti-6Al-4V strap joints are similar implicating that the higher scarf angle designs can be replaced with Ti-6Al-4V straps for better repair efficacy. Failure analysis depicts that delamination due to the inner edge peel stresses is a critical failure mode of the strap repaired joints.